Visual Management of Daily Construction Site Space Use - Bascoul, Audrey M.; Tommelein, Iris D.; Douthett, Danielle (Frontiers in Built Environment, 2020)
Space is a construction resource not to be overlooked during project scheduling, production planning, and control. When space use over time is not planned, trades may get stacked in areas of the jobsite that are labor intensive, which may hamper productivity and cause safety concerns. Augmenting traditional scheduling representations, spatiotemporal modeling in construction considers both space and time to depict ongoing construction work. This paper presents a simple space scheduling program called LoSite that helps workers involved in doing the work visualize the work schedule, facilitates production control, and fosters transparency in daily coordination of work space among trades. LoSite was implemented in Microsoft Excel. The researchers prototyped, deployed, and tested the space scheduling program to visualize construction work being done during the interiors phase of an open-space office building. Successes of the program as well as limitations to its full adoption by the team are discussed in this paper. LoSite delivers proof-of-concept that space-use visualization, even on a large-scale project, can be accomplished effectively using software that is readily available and familiar to many people.